Assessment of a plasmid conjugation procedure to monitor horizontal transfer of an extended-spectrum β-lactamase resistance gene under food chain scenarios - Adrián Alvarez-Molina; Elena Trigal; Miguel Prieto; Mercedes López; Avelino Alvarez-Ordóñez (Current Research in Food Science, 2023)
Plasmids are relevant reservoirs of antimicrobial resistance genes (ARGs) which confer adaptive advantages to their host and can be horizontally transferred. The aims of this study were to develop a conjugation procedure to monitor the horizontal transfer of a 193 kb plasmid containing the extended-spectrum β-lactamase production gene blaCTX-M-14 between two Escherichia coli strains under a range of food chain-related scenarios, including temperature (20–37 °C), pH (5.0–9.0) or the presence of some biocidal agents (benzalkonium chloride, sodium hypochlorite or peracetic acid). The average conjugation rate in LB broth after 18 h at 37 °C was 2.09e-04 and similar rates were observed in a food matrix (cow's milk). The conjugation was reduced at temperatures below 37 °C, at alkaline pH (especially at pH 9.0) or in the presence of benzalkonium chloride. Peracetic acid and sodium hypochlorite slightly increased conjugation rates, which reached 5.59e-04 and 6.77e-03, respectively. The conjugation procedure described can be used to identify risk scenarios leading to an enhanced ARGs transmission via plasmid conjugation, as well as to identify novel intervention strategies impairing plasmid conjugation and tackling antimicrobial resistance.